Antimicrobial susceptibility and distribution of non-typhoidal Salmonella serovars isolated in Malaysian children - Lee, Way Seah; Puthucheary, S.D.; Parasakthi, N.; Choo, K.E. (2003)
There is widespread resistance of Salmonella species to commonly prescribed antimicrobials the world over. We aimed to determine the antimicrobial susceptibility and serovar distribution of non-typhoidal Salmonella (NTS) isolated from blood cultures of Malaysian children. Positive isolates of NTS from blood cultures obtained from children admitted to the pediatric wards of University of Malaya Medical Center (UMMC), a large urban hospital from Kuala Lumpur (1991-2001), and Hospital Kota Bharu (HKB), from the predominantly rural state of Kelantan (1991-1999), Malaysia, were reviewed retrospectively. Serovar distribution and antimicrobial susceptibility were ascertained. A total of 64 and 55 isolates of NTS were obtained from blood cultures of children admitted to UMMC and HKB, respectively. The commonest serovar isolated was Salmonella enteritidis in both centers. The NTS isolated were highly sensitive to the antimicrobials tested: ampicillin 98 per cent, chloramphenicol 98 per cent, gentamicin 97 per cent, trimethoprim-sulfamethoxazole (TMP-SMX) 98 per cent, and ceftriaxone 100 per cent in UMMC; ampicillin 100 per cent, chloramphenicol 87 per cent, kanamycin 100 per cent, streptomycin 96 per cent, TMP-SMX 93 per cent, and tetracycline 89 per cent in HKB. There were only one and five multi-resistant isolates in UMMC and HKB, respectively. In conclusion, NTS isolated from blood cultures of Malaysian children from Kuala Lumpur and Kota Bharu were highly sensitive to commonly prescribed antibiotics. We speculate that this is due to the restriction of sales of antimicrobials in Malaysia except by prescription. Continuing vigilance and frequent antimicrobial surveillance is necessary.